Initial clinical experience of using a newly designed preshaped microguidewire in acute endovascular thrombectomy - Ohshima, Tomotaka; Kawaguchi, Reo; Maejima, Ryuya; Yukiue, Naoto; Matsuo, Naoki (Asian Journal of Neurosurgery, 2020)
Mechanical thrombectomy has been widely used for the treatment of acute ischemic stroke. During this procedure, operators must navigate the microcatheter with a microguidewire (MGW) into vessels that cannot be visualized on fluoroscopy as rapidly as possible. In this study, we developed a modified pigtail-shaped MGW (MPMGW) for security and controllability. Moreover, the efficacy of the MPMGW for the treatment of acute ischemic stroke was assessed. The MPMGW was designed using 0.014 MGW. Because we created four MPMGWs during a clinical evaluation before the launch in the market, these wires were used in four consecutive patients with acute ischemic stroke in the single institution. The occluded arteries were the basilar artery (n = 1), middle cerebral arteries (M1 and M2, n = 2), and internal carotid artery (n = 1). All four procedures were conducted without any complications. The procedures included navigating the MGW and passing it through the clot. Complete recanalization was achieved in all cases. The average time between femoral artery puncture and recanalization was 15 min. The use of the preshaped MPMGW in acute thrombectomy was effective in terms of both security of procedure and reduction in recanalization time.
Keywords: Acute ischemic stroke; endovascular treatment; microguidewire; modified pigtail-shaped; preshape; thrombectomy